The Effect of Students’ Resiliency and Self-Efficacy on Academic Stress During the Transition Period from Online to Offline Learning - Aprianti, Melani; Syakina, Dina; Hastyanadi, Faurezia Chinta; Puspitasari, Vina (Jurnal Sains Psikologi, 2024)
The transition of learning from online to offline has an impact that can be a problem for its implementation if students cannot adapt properly. The low ability of students in the adaptation process will cause negative reactions that arise not only from physical reactions but also psychologically due to academic demands and pressure to adapt quickly to environmental changes. This situation makes students vulnerable to experiencing academic stress. This research aims to see the relationship between academic resilience and academic self-efficacy of students in dealing with academic stress due to the transition of the learning system. Academic resilience is measured using the Academic Resilience Scale (ARS-30), academic self-efficacy is measured using The Academic Self-Efficacy Scale (TASES), and academic stress is measured using the academic stress inventory. The sample was 354 students of University X. The data were analyzed using multiple regression analysis techniques. The results showed that academic resilience and academic self-efficacy predicted academic stress (R-squared equals .137; p less than .01) during the transition from online to offline learning.